3rd International Conference on Nanotechnologies and Biomedical Engineering ICNBME-2015, September 23-26, 2015, Chisinau, Republic of Moldova - Sontea, Victor; Tiginyanu, Ion (IFMBE Proceedings, 2016)
This volume presents the proceedings of the 3rd International Conference on Nanotechnologies and Biomedical Engineering which was held on September 23-26, 2015 in Chisinau, Republic of Moldova. ICNBME-2015 continues the series of International Conferences in the field of nanotechnologies and biomedical engineering. It aims at bringing together scientists and engineers dealing with fundamental and applied research for reporting on the latest theoretical developments and applications involved in the fields. Topics include Nanotechnologies and nanomaterials Plasmonics and metamaterials Bio-micro/nano technologies Biomaterials Biosensors and sensors systems Biomedical instrumentation Biomedical signal processing Biomedical imaging and image processing Molecular, cellular and tissue engineering Clinical engineering, health technology management and assessment; Health informatics, e-health and telemedicine Biomedical engineering education Nuclear and radiation safety and security Innovations and technology transfer.